Produção, isolamento e identificação de colorantes produzidos por fungos isolados de amostras do solo amazônico - Oliveira, Luciana Aires de (2017)
Synthetic dyes when used in over, may cause some toxic effects to health, such as mutagenicity, carcinogenic potential, hyperactivity in children, urticaria, stomach ache and vomit. Fungal dyes are an alternative to synthetic ones because they have the potential to present lower toxicity, greater biodegradability, besides being able to possess antimicrobial, antioxidant and anticancer activities. However, few studies have investigated the potential of the Amazonian fungi for dye production. The purpose of the present study were to produce, isolate and identify dyes produced by fungi from Amazonian soil. Two hundred fungal isolates obtained from samples of Amazonian soil and belonging to the Collection of Microorganisms of INPA were used in this study. The isolates were evaluated for their ability to produce dyes. The isolates that showed the most intense dyes were submitted to a submerged bioprocess and identified by sequencing of the ribosomal DNA ITS region. The most intense colorant produced by one of the fungi tested in these bioprocesses was subjected to preparative chromatography (thin-layer chromatography and column chromatography) and the isolated dye was identified by spectrophotometric methods (1H-NMR and 13C-NMR) and mass spectroscopy. Univariate experiments were performed to evaluate the influence of different bioprocess factors on dye production. As main results, we observed that of the 200 strain investigated, 45 were able to produce dyes. The strains Penicillium sclerotiorum LM 5679, Penicillium sp. LM 5903 and Penicillium sp. LM 5924 stood out producing the most intense dyes. The colored substance produced by Penicillium sclerotiorum LM 5679 has been isolated and chemically identified as an alkylresorcinol (5-pentadacylresorcinol). Regarding the influence of the bioprocess factors, sucrose, yeast extract and sodium nitrate increased production the dye. In view of the above results, the fungi of the Amazonian soil are potential producers of dyes and further studies on the stability, toxicity and applicability of these compounds are necessary for their subsequent insertion in the market. Keywords: Colorants, chemical characterization, bioprocess factors, Amazonian soil.